Cellular distribution and linkage of D-(-)-3-hydroxy fatty acids in Bacteroides species. - Mayberry, W R (1980)
Two strains of Bacteroides asaccharolyticus and two strains of Bacteroides fragilis were analyzed for total fatty acid, total lipid fatty acid, and total bound fatty acid profiles. Extracted lipids and defatted cell residues were subjected to sequential alkaline and acid methanolyses to distinguish ester- and amide-linked fatty acids in each fraction. In the lipid fractions, all the ester-linked fatty acids were nonhydroxylated, whereas all of the amide-linked fatty acids were hydroxylated. In the nonextractable fractions, both hydroxy and nonhydroxy fatty acids were found in both ester and amide linkage, although hydroxy acids predominated. The fatty acid profiles of the bound fractions differed widely from those of the lipid fractions. Bound fatty acid represented approximately 10% of the total cellular fatty acids.